Modelling the structure of sludge aggregates. Issue 9 (2nd May 2016) - Smoczyński, Lech; Ratnaweera, Harsha; Kosobucka, Marta; Smoczyński, Michał; Kalinowski, Sławomir; Kvaal, Knut
ABSTRACT: The structure of sludge is closely associated with the process of wastewater treatment. Synthetic dyestuff wastewater and sewage were coagulated using the PAX and PIX methods, and electro-coagulated on aluminium electrodes. The processes of wastewater treatment were supported with an organic polymer. The images of surface structures of the investigated sludge were obtained using scanning electron microscopy (SEM). The software image analysis permitted obtaining plots log A vs. log P, wherein A is the surface area and P is the perimeter of the object, for individual objects comprised in the structure of the sludge. The resulting database confirmed the 'self-similarity' of the structural objects in the studied groups of sludge, which enabled calculating their fractal dimension and proposing models for these objects. A quantitative description of the sludge aggregates permitted proposing a mechanism of the processes responsible for their formation. In the paper, also, the impact of the structure of the investigated sludge on the process of sedimentation, and dehydration of the thickened sludge after sedimentation, was discussed.